(untitled) (Eurasian Research Bulletin, 2021)
In this paper presents the reliability mathematical formula of Frechet Cascade model . The reliability of the model is expressed by Frechet random variables, which are stress and strength distributions. The reliability model was estimated by seven dissimilar methods ( ML , Mo , LS , WLS , Rg ,Pr and Pi ) and simulation was performed using MATLAB 2012 program to compare the results of the reliability model estimates using the MSE criterion , the results indicated that the best estimator among the seven estimators was ML and Pi .